Cost-efficient multiport DC circuit breaker with integrated power flow control for HVDC grids - Yunfeng Huang; Huangqing Xiao (International Journal of Electrical Power & Energy Systems)
To address the technical challenges of fast DC fault interruption and power flow control in DC grids, this paper proposes a multiport DC circuit breaker (CB) topology with power flow control (PFC) capability and designs two control strategies: a PFC mode and a CB mode. The proposed circuit topology integrates both functions through topological similarity, resulting in high reuse of power electronic devices and superior economic efficiency. The control strategy for the PFC mode independently regulates the capacitor voltage and the current of each line, solving the issue of poor applicability of conventional power flow control methods in multiport scenarios. The control strategy for the CB mode ensures fast mode switching and timely fault interruption. A four-terminal DC grid simulation model was built in PSCAD/EMTDC to validate various operating conditions. The results demonstrate that the proposed multiport DC CB with PFC capability can rapidly and accurately track the reference value of the line power flow under normal operation using the PFC mode. In the event of a fault, it quickly switches to the CB mode to clear the fault, and after fault interruption, it can restart the PFC mode to regulate the power flow of the healthy lines.